GOVERNANCE PRACTICES GOVERNMENT, OF ACCOUNTABILITY PERFORMANCE AND IMPLEMENTATION OF RISK MANAGEMENT AND IMPLICATIONS FOR FRAUD DETECTION AND PREVENTION - David - Pangaribuan (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The development of science, information and communication technology triggered a growing public awareness of intelligent, critical and realistic demand the rights and involvement in the governance of government that is clean, orderly and trustworthy. This study aims to explore the influence of government governance, risk management and performance accountability system to the detection and prevention of fraud in local government Banten Province. Population Research is working units in the Banten Provincial Government as much as 23 units. The sampling method using purposive sampling, the type of research is quantitative with primary data types. Methods of data collection using a questionnaire distributed directly to the respondents as much as 4-5 questionnaires at each work unit. Respondents are structural official echelon II, III and IV in each unit and the respondents as many as 94 people. The data were processed using SPSS version 22, which is used to test the research hypothesis. Results revealed that the implementation of government governance, risk management and performance accountability system has positive influence on the detection and prevention of fraud in the financial governance of the regional government of Banten Province. Results reinforce the theory that the detection and prevention of fraud need to be committed to implementing government governance, risk management and performance accountability system. Implications The study provides guidelines and principles of governance and financial governance system is orderly, disciplined and trustworthy. Foster awareness of government officials the importance of risk culture within the organization in order to avoid conflict of interest and focus on achieving the main objectives of the government. Encourage synergy among units in order to achieve a system of planning, budgeting, measurement and performance evaluation in an integrated and sustainable. The next study used a qualitative approach in the prevention of fraud.